Análisis socioeconómico de los comerciantes informales del sector Santa Marianita de Jesús del cantón Salitre - Aguirre Macías, Amy Emilia (2024)
The purpose of this research is to analyze the socioeconomic situation of informal traders within the Santa Marianita sector of the Salitre canton, since during the study it has been possible to observe a large number of informal traders who at the end of the day have not been able to market their products. Therefore, a methodology is used under the mixed nature approach, that is, qualitative and quantitative, since a survey was carried out on tourists who frequent the Santa Marianita de Jesús sector of the Salitre canton, which are considered as population and study sample. Among the results, it was found that informal traders show resilience and the ability to adapt to economic crises, therefore, they need support to formalize and improve their businesses, with tools and resources so that informal traders can grow and prosper.